A CRITICAL DISCOURSE ANALYSIS OF AHMAD AL-SHARA’S SPEECH IN BUILDING NATIONAL IDENTITY IN POST-CONFLICT SYRIA - Firmansyah, Muhammad; Naufal Muhammad Fadhurrahman (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2026)
This study analyzes how Ahmad al-Shara’s political speeches construct a new national identity in Syria in the post-conflict context and the transition of power following the fall of the Bashar al-Assad regime. This study uses a qualitative descriptive approach with Norman Fairclough’s Critical Discourse Analysis (CDA) framework, which encompasses three analytical dimensions: text, discourse practice, and sociocultural practice. The research data consists of three official speeches by Ahmad al-Shara delivered during the early period of the transitional leadership and obtained from Arabic media broadcasts. They are then transcribed, translated, and analyzed based on lexical choices, rhetorical strategies, discourse production-consumption processes, and the underlying socio-political context. The results indicate that these speeches reproduce Syrian national identity through a combination of discourses of religiosity, nationalism, and narratives of collective suffering. Linguistic strategies such as the use of emotive diction, the metaphor of the "nation’s wound," and the parallel use of masculine and feminine forms serve to construct a message of inclusivity, social reconciliation, and the legitimacy of moral leadership. These findings suggest that Ahmad al-Shara’s political speeches not only function as a political communication tool but also as a discursive practice to reframe Syrian national identity amidst the post-conflict recovery process.